Can dissipation prevent explosive decomposition in high-energy heavy ion collisions? - Fraga, E. S.; Krein, G. (Elsevier B.V., 2005)
We discuss the role of dissipation in the explosive spinodal decomposition scenario of hadron production during the chiral transition after a high-energy heavy ion collision. We use a Langevin description inspired by microscopic nonequilibrium field theory results to perform real-time lattice simulations of the behavior of the chiral fields. We show that the effect of dissipation can be dramatic. Analytic results for the short-time dynamics are also presented. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: QCD phase transition; heavy-ion collisions; spinodal decomposition; dissipation in field theory